Publicity and Egalitarian Justice - Lippert-Rasmussen, Kasper (Journal of moral philosophy, 2008)
Abstract Recently, the issue of publicity has surfaced in discussions of the correct interpretation of the Rawlsian principles of justice. In an intriguing critique of G.A. Cohen's preferred interpretation of the difference principle as a principle that is incompatible with incentive-based inequalities, Andrew Williams points to a gap in Cohen's argument, alleging that Cohen's interpretation of the difference principle is unlikely to be compatible with the Rawlsian endorsement of publicity. Having explored a possible extrapolation of Cohen's critique to aggregate consumer choices and a resulting extension of Williams's charge that the difference principle, on Cohen's reading, fails to meet the publicity constraint because of its informational demandingness, I defend three claims: (a) it is doubtful that Rawls endorses a publicity constraint of the sort that would rule out Cohen's interpretation of the difference principle; (b) it is hard to see how such a constraint could emerge from the considerations Rawls offers in favour of publicity; and (c) under certain interpretations, the difference principle disallows incentive-based inequalities and yet satisfies suitably modest versions of the publicity constraint.